An ADDIE-Based Digital Learning Content Framework for Islamic Religious Education: Designing Interactive, Accessible, and Values-Integrated Learning in Indonesian Secondary Schools - Udin; Patimah, Siti; Murtafiah, Nurul Hidayati (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This design and development study develops an ADDIE-based framework for digital learning content in Islamic Religious Education (IRE). The study responds to a persistent gap in which digital resources are often added as technical supplements rather than designed as coherent environments that connect Islamic values, learner activity, accessibility, and formative feedback. A document-informed design audit of the original development problem and contemporary research was used to define learning requirements, develop a content architecture, and specify an implementation and evaluation protocol. The resulting framework integrates six design components: contextual learner analysis, explicit outcomes, multimodal source-based learning, interactive application tasks, guided reflection, and evidence-rich formative feedback. The framework also embeds accessibility provisions, including low-bandwidth alternatives, mobile-first delivery, readable visual hierarchy, and flexible participation routes. Results are presented as design outputs rather than causal claims because the original project record did not contain participant-level validation or outcome data. The study contributes a values-integrated digital pedagogy model for Indonesian secondary education, including Islamic vocational secondary schools and Islamic boarding schools (pesantren) where locally appropriate. Its principal implication is that digital IRE content should be developed as an iterative pedagogical system, not as a collection of media files.